Temperature in Semi-infinite and Finite Cylinder with Moving Heating Over the Lateral Surface - Tróżnowski, T. (Engineering Transactions, 1986)
In this paper some relations describing a nonstationary temperature field in a semi-infinite and also a finite cylinder heated over a part of its lateral surface with a moving axialsymmetric thermal surface source and dependent on two cases of boundary conditions across the face plane; the temperature is equal to zero and there is perfectly thermal insulation, are derived. On the basis of the fundamental solution for a long cylinder in [1] a computer program has been made and the results have been widely analysed in [3]. The formulae of the temperature for various kinds of heating have been given. The temperature distribution within the cylinder of length L is presented as an infinite sum of elements being the fundamental solution alike. Finally, a transformation to Green's function as a limiting case of results has been proved. Numerical results are given.